Midfrontal theta oscillations and conflict monitoring in children and adults. Issue 8 (23rd November 2021) - Chevalier, Nicolas; Hadley, Lauren V.; Balthrop, Kullen
Abstract: Conflict monitoring is central in cognitive control, as detection of conflict serves as a signal for the need to engage control. This study examined whether (1) midfrontal theta oscillations similarly support conflict monitoring in children and adults, and (2) performance monitoring difficulty influences conflict monitoring and resolution. Children ( n = 25) and adults ( n = 24) completed a flanker task with fair or rigged response feedback. Relative to adults, children showed a smaller congruency effect on midfrontal theta power, overall lower midfrontal theta power and coherence, and (unlike adults) no correlation between midfrontal theta power and N2 amplitude, suggesting that reduced neural communication efficiency contributes to less efficient conflict monitoring in children than adults. In both age groups, response feedback fairness affected response times and the P3, but neither midfrontal theta oscillations nor the N2, indicating that performance monitoring difficulty influenced conflict resolution but not conflict monitoring.